Psicologia e lazer: um estudo sobre o tempo liberado da escola da infância contemporânea - Michelle Araujo Rocha (2011)
This study attempted to identify and describe the time dedicated to after-school activities by nine and ten year-olds enrolled in 4th grade in one private and one public school located in Belo Horizonte, Brazil, and then conduct the analysis of these activities by trying to stablish a connection between them and these childrens development. Theoretical and empirical background were grounded in Positive Psychology, Leisure Studies, childhood and extracurricular activities, and discussed with focus on field research. Data was gathered from 20 children in one public school and 21 children in one private school, who engaged in individual, semi-structured interviews. Children´s answers were recorded, transcribed, and later analyzed through a qualitative and quantitative approach using Content Analysis. Response categories were created based on similar thematic units, and the frequency of answers was calculated for each category. Gender and school type comparisons were carried out. The four most frequent after-school activities were: watching television, doing homework, using the computer, and playing video-games, mostly reported by children from the private school. These four activities are associated with sedentariness which decreases motor activity and can contribute to child obesity, delay in the motor development and other negative outcomes. Social conditions such as land speculation, increase in urban traffic, presence of community-based violence and labor, may have determined the quality of many leisure experiences, moving them into peoples homes, reducing social exchange in public places. Only three children from the public school indicated structured after-school classes as an extracurricular activity. Financial hardship may account for this low frequency. Some children from the private school mentioned taking part in three or four after-school activities, but most of them participate in at least one. This engagement in after-school programming suggests a systematic intention to prepare students in private school for their academic/professional future. The results also demonstrated that the responsibility of performing domestic chores and of taking care of family members was mostly given to girls from the public school, who reported spending a considerable part of their day involved with these activities. Many girls value these tasks because they believe them to be useful for their adult lives. Poor parental participation in childrens activities was noted. Weekend family leisure experiences seem to prioritize parental needs, giving children a secondary role in the family. Finally, leisure may contribute as a resource for strengthening family relationships. Moreover, extracurricular activities can promote pleasant group leisure practices by helping to cultivate skills that facilitate personal development, leading individuals (children) and groups (families) to happiness.